United by Violence, Divided by Cause? A Comparison of Drivers of Radicalisation and Violence in Asia and Europe - Waha, La Toya (Nomos Verlagsgesellschaft mbH & Co. KG, 2020)
Zusammenfassung Politische Gewalt gibt es überall. Aber wie und wieso entsteht sie, und was kann sie verhindern? Dieses Buch befasst sich mit der Vielfalt politischer Gewalt in Westeuropa, Süd- und Südostasien sowie der Vielfalt ihrer Begründungen. Es bietet Einblicke in verschiedene ideologische, strukturelle, soziale und politische Hintergründe, Beziehungen und Ziele von nicht-staatlichen Gewaltakteuren in Asien und Europa. Dabei werden verschiedene disziplinäre und theoretische Ansätze sowie eine Vielzahl an Fallbeispielen vorgestellt. Ziel des Bandes ist es, Phänomene zu vergleichen und vereinfachten, eindimensionalen Erklärungen, warum nicht-staatliche Akteure Gewalt anwenden, komplexere Erklärungsansätze entgegenzusetzen. Abschließend bietet das Buch Empfehlungen für politisches Handeln an. Mit Beiträgen von Greg Barton, D. SubaChandran, Aurel Croissant, Rohan Gunaratna, Kevin McDonald, Subrata K. Mitra, Khuram Iqbal, Serina Rahman, La Toya Waha und Christian Echle Abstract Political violence is everywhere. But how does it emerge and what can be done about it? This book addresses the diversity of violence in South Asia, South East Asia and Western Europe. It examines the various forms of ideological backgrounds, structural conditions, relations and aims of non-state actors who are involved in violence in these regions and certain countries. Thereby, this book presents a similar diversity of theoretical and disciplinary approaches towards explaining the same phenomenon: violence. The rationale behind this collection of approaches and case studies is to identify communalities on the one hand, and to counter simple, unidimensional explanations of why non-state actors resort to violence on the other. Finally, it provides policy recommendations on how to counter violence. With contributions by Greg Barton, D. SubaChandran, Aurel Croissant, Rohan Gunaratna, Kevin McDonald, Subrata K. Mitra, Khuram Iqbal, Serina Rahman, La Toya Waha and Christian Echle